Pengembangan dan Evaluasi Sistem Pengelolaan Hafalan Juz 30 Mahasiswa Berbasis Mobile - Ayni, Nurul; Faisal, Faisal; Baharuddin, Hastuti (Subaltren Inti Media, 2025)
The Information Systems Study Program at the State Islamic University (UIN) Alauddin Makassar offers a course on Ilmu Tajwid, which is the study of the rules of Qur’anic recitation. Several challenges are commonly encountered, including scheduling conflicts between students and lecturers, which often hinder students from submitting their memorized recitations. Additionally, the memorization records are still managed manually, posing risks of data being misplaced or lost. Therefore, the purpose of this study is to improve and overcome the limitations of the manual submission system by developing an online submission system with video features and digital record-keeping. This research employs a descriptive qualitative approach, utilizing data collection methods such as observation, interviews, and literature study. The system design for managing the Ilmu Tajwid course and student memorization uses the waterfall model. The application was developed using the Flutter framework, and the system was tested using the System Usability Scale (SUS) method. The result of this research is a mobile-based system that achieved a final SUS score of 88.5, indicating that the application is effective for the submission and monitoring of Juz 30 memorization in the Information Systems Study Program.